The extent of rights under the SOEKOR leases - Schippers, Ashton (Department of Public Law, 2023)
The adoption of the Third United Nations Convention on the Law of the Sea1 has revolutionized international approaches to the regulation of the world's oceans. Although the convention is not yet in force, some of its provisions can be regarded as international customary law, in particular, its provisions on the expansion of coastal state jurisdiction. The exploitation of hydrocarbon resources off the South African coast in the vicinity of Mossel Bay presents new opportunities and challenges for this country, especially in the sphere of technology. The venture involves astronomical costs, and a major development of the relevant areas as is evident from the following: The cost aspect is becoming "an even greater Frankenstein 2 monster" . In 1985, the Minister of Energy Affairs Danie Steyn publicly quantified the project at R4800m. Those figures were based on a 40c US$ exchange rate and included Rl 700m for a refinery. The Minister's pre-election announcement in 1987 was that the cost of the project would be R5500m only for the offshore development. Later those figures were clarified as R4193m for the so-called FA gas field and R1307m for the so-called EM gas field3 • On 27 April 1988, the Mossgas project received Cabinet approval. The cabinet ordered a rework of the cost factor and SOEKOR estimated the figure on both the 4 on-shore and off-shore stages at R5300m A new industrial area will flank the site for Mossel Bay's refinery. This area will extend to a rail line in the north. New harbour facilities which will include a support 5 infrastructure for offshore operations, are planned ( 2 ) Work has started on a new dam to supply water to the plant and Escom is extending its supply of electricity to the area. Various residential and business areas are being extended and developed with adjacent areas such as George developing into a strategic alternative for the long-term South Coast gas industry6. It is estimated that the first gas will come ashore on 1 June 1991 and that for the next 35 years Mossgas will produce 25000 barrels a day from its offshore reservoirs. Research has shown that the South Coast seems more like the North Sea. "Initially close in-shore finds were mainly gas as the search moved into deeper water the hydrocarbon mix became more 'l 7 II 01. It is against this background that the extent of rights under the SOE KOR leases will be examined. The discussion in this paper is limited to certain provisions embodied in the Prospecting Lease (PL) and the Mining Lease (ML) entered into between SOEKOR and the government in terms of the Mining Rights Act 20/1967.